Telaah Ayat Al-Qur`an dan Hadits Tentang Akal Manusia - Silviana Annisa; Wiramayasari; Alihan Satra (Advances In Education Journal, 2026)
Reason is a gift from Allah SWT that distinguishes humans from other creatures and is an important tool in understanding the truth and living life according to religious guidance. This study aims to examine the concept of human reason from the perspective of the Qur'an and Hadith, including its definition, position, function, commands for the use of reason, and its limitations in understanding Islamic teachings. This study uses a library research method with a descriptive qualitative approach. Data were obtained from relevant verses of the Qur'an, hadith, commentaries, books, and scientific journals, then analyzed using content analysis techniques. The results show that Islam gives a very high position to reason and encourages humans to use it to understand the signs of God's greatness, develop knowledge, and distinguish between right and wrong. The Qur'an repeatedly commands humans to think, reflect, and learn lessons from various natural and life phenomena. However, reason has limitations, especially in understanding supernatural matters that are beyond human reach. Therefore, the use of reason must always be in harmony with revelation, namely the Quran and Hadith, in order to produce correct understanding and strengthen faith in Allah SWT.